Healthy, inclusive, and sustainable metropolises: New strategies for transdisciplinary dialogues in Munich, Germany - Davis, Alicia; Kretschmann, Nicolas; Planötscher, Nadja; Janssen, Christian (Utan Kayu Publishing, 2023)
According to the United Nations, within the next decades approximately 70% of the world’s population will become urban citizens. This massive immigration results in urbanization trends of the outskirts and furthermore neighboring districts merge with the urban space, presenting enormous environmental, ecological, health-related, and social challenges to the regions and their citizens. Politics will have to face these issues, but so far, the urban planning and environmental oriented interdependencies are not notably considered and on a municipal level essential resources are disregarded. Within the timeframe of three years (2020-2022), the Munich University of Applied Sciences assessed in a collaborative process the urban potentials of a metropolitan district and developed health-promoting and sustainable building and open space structures for the year 2050. Therefore health, participation, urbanity, and sustainability issues were interlinked and integrated in the urban development process. The research project is based on an inter- and transdisciplinary approach, which furthermore includes different stakeholders from economy, politics, and the civil society.